Sustainable Energy Consumption and Society Personal, Technological, or Social Change? - Goldblatt, David L.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2005)
What drives developed countries' high rates of energy and resource consumption? How important are individual efforts versus technological or social innovations for environmental sustainability? A multidisciplinary study combining social science, energy analysis, and risk communication, this work occupies a unique niche in the literature. Few treatments of energy and the environment approach the problem through the larger social science framework of sustainable consumption, while sociological studies of consumption eschew quantitative modelling. This book incorporates both, using theories, research, and computer-aided interviews to illustrate the range and relative effectiveness of interventions that support sustainable energy consumption. Based on award-winning research at the Swiss Federal Institute of Technology, this book should be of interest to academics, agencies, and activists working on the interaction of energy, the environment, and society. It is also readily accessible to the group it is primarily concerned with: the educated lay public.
Sustainable Consumption and the Public's Room to Maneuver in Energy Use -- Targets of Intervention for Sustainable Consumption -- Energy, Environment, and Society -- Field Study with Computer-Aided Interviews -- Achievements, Open Questions, and Lessons Learned.
Keywords: ENGINEERING; ENVIRONMENTAL SCIENCES; CLIMATIC CHANGES; ENVIRONMENTAL PROTECTION; SOCIOLOGY; ENGINEERING; RENEWABLE ENERGY SOURCES; ENVIRONMENT, GENERAL; ATMOSPHERIC PROTECTION/AIR QUALITY CONTROL/AIR POLLUTION; CLIMATE CHANGE; ENVIRONMENTAL MONITORING/ANALYSIS.; SOCIOLOGY